Cesarean Section or Instrumental Delivery: The Best Choice for Mode of Delivery during Second Stage of Labor - Rawal, Suniti; Katuwal, Neeta; Shrestha, Sajana (Journal of Institute of Medicine Nepal, 2020)
Introduction Managing second stage of labour is very crucial. Emergency Cesarean Section (CS) or Instrumental Delivery (ID) is the only choices although complications might occur in both modes of deliveries. The rate of CS is at rise and the fear of failed ID followed by emergency CS with added complications makes the choice more difficult amongst the obstetricians. Methods A retrospective study done to assess the maternal and fetal outcome in second stage of labour following ID and emergency CS from April 2018 to March 2019 among the pregnant women having completed 34 weeks of gestations and beyond. Results Of 4761 deliveries, 2537 (53.2%) were vaginal and 2224 (46.7%) CS, and amongst all, 133 (2.7%) were second stage interventions. Out of 133, 78 had ID, 76 were successful and 2 failed. Fifty seven (2.6%) were second stage CS. Nulliparas (65.8%) needed more ID, teenage pregnancy (6.5%) (p=0.04) and heart disease (18.4%) (p=0.002) were high risk for ID. Complications were more in CS, uterine extensions, (29.8%) (p<0.001), urinary complications, (43.9%) (p<0.001) and blood loss (p<0.001). Neonatal admission too was higher in CS (n=29) and more so due to respiratory distress (16/29). Conclusion Despite of few failed attempted ID, it still proved to be better choice for delivery during second stage, as both maternal and neonatal complications were higher following the second stage CS. Hence, the correct and timely decision for ID addressing the associated risk factors could lead to favorable outcome.